2017
DOI: 10.1097/spv.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Rectovaginal Fistula Repair

Abstract: Recurrence rates after RVF repair are high and did not differ by fistula etiology. Abdominal repair of RVF had significantly fewer recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In Mayo Clinic series, it was reported that 54% of their patients' RVF were due to inflammatory bowel disease whereas 11% were secondary to other reasons (16). Similarly, in our series, 50% (n=3) of patients' RVF were secondary to CD.…”
Section: Discussionsupporting
confidence: 73%
“…In Mayo Clinic series, it was reported that 54% of their patients' RVF were due to inflammatory bowel disease whereas 11% were secondary to other reasons (16). Similarly, in our series, 50% (n=3) of patients' RVF were secondary to CD.…”
Section: Discussionsupporting
confidence: 73%
“…Gynecologic surgeons typically approach distal fistulae through a transvaginal approach, while colon and rectal surgeons may utilize a transperineal or endorectal approach. Definitive procedures, including pelvic exenteration and abdominoperineal resection, are more commonly utilized for RVF secondary to pelvic malignancy, when tissue compromise is likely …”
Section: Surgical Considerations and Treatmentmentioning
confidence: 99%
“…Definitive procedures, including pelvic exenteration and abdominoperineal resection, are more commonly utilized for RVF secondary to pelvic malignancy, when tissue compromise is likely. 40 An abdominal approach is most often required for the surgical treatment of colovaginal fistulae. Once the rectum and vagina are separated, the defects are debrided and closed in layers.…”
Section: Surgical Considerations and Treatmentmentioning
confidence: 99%
“…Even though it is benign, the distressing and persistent symptoms interfere with daily activities and sexual life, and have a long-term potential detrimental impact on psychological health[ 2 , 3 ]. Obstetric trauma is the primary etiological factor for RVF, but it can also be acquired from local abscess, pelvic floor or rectal surgery, trauma, or radiotherapy[ 3 - 5 ]. Chronic inflammatory bowel disease (most commonly Crohn’s disease) is the second most common etiology with rates varying between 6% and 23%[ 6 ].…”
Section: Introductionmentioning
confidence: 99%